Price adjustment in the euro area in the low-inflation period: Evidence from consumer and producer micro price data - Erwan Gautier; Peter Karadi; Jurgen Amann; Cristina Conflitti; Riemer P. Faber; Brian Fabo; Ludmila Fadejeva; Catherine Fuss; Theodora Kosma; Valentin Jouvanceau; Fernando Martins; Jan-Oliver Menz; et al. (European Central Bank (ECB), 2023)
This paper documents five stylised facts relating to price adjustment in the euro area, using various micro price datasets collected in a period with relatively low and stable inflation. First, price changes are infrequent in the core sectors. On average, 12% of consumer prices change each month, falling to 8.5% when sales prices are excluded. The frequency of producer price adjustment is greater (25%), reflecting that the prices of intermediate goods and energy are more flexible. For both consumer and producer prices, cross-sectoral heterogeneity is more pronounced than cross-country heterogeneity. Second, price changes tend to be large and heterogeneous. For consumer prices, the typical absolute price change is about 10%, and the distribution of price changes shows a broad dispersion. For producer prices, the typical absolute price change is smaller, but nevertheless larger than inflation. Third, price setting is mildly state-dependent: the probability of price adjustment rises with the size of price misalignment, mainly reflecting idiosyncratic shocks, but it does not increase very sharply. Fourth, for both consumer and producer prices, the repricing rate showed no trend in the period 2005-19 but was more volatile in the short run. Fifth, small cyclical variations in frequency did not contribute much to fluctuations in aggregate inflation, which instead mainly reflected shifts in the average size of price changes. Consistent with idiosyncratic shocks as the main driver of price changes, aggregate disturbances affected inflation by shifting the relative number of firms increasing or decreasing their prices, rather than the size of price increases and decreases.
Keywords: E3; E5; 330; price stickiness; consumer prices; producer prices; scanner data